Developing EFL Learners’ Writing Ability and Reading Comprehension by Using Communicative Language Teaching through Small Group Discussion - Khairan Hidayat; Muhammad Fajri Hamdy (English Instruction, 2020)
This research aimed to find out the significant effect of using CLT through small group discussion on students’ writing and reading skills at SMAN 1 Kampar Timur. It was carried out by using a quasi-experimental design. The research sample was 72 tenth-graders who were selected from 201 students at the school. Furthermore, they were divided into two groups, namely the experimental and the control group. In the process of data collection, tests and observations were utilized. In analyzing the collected data, statistical analyses including t-tests for independent and paired samples and effect size formula were used. Finally, it was found out that the significance values were 0.000 and 0.000 for both skills respectably and they were smaller than the probability value, p (0.005). In addition to the effect size obtained (writing: 0.5 and reading: 0.5), it was inferred that CLT through small group discussion had significantly affected students’ skills in writing and reading comprehension to the extent that average students in the experimental group improve their both skills ability similar to big five students in the control group. Moreover, findings suggested that CLT through small group discussion might be applied in teaching and learning of writing and reading for various sample characteristic in different areas and contexts in Indonesia.